1997
DOI: 10.1177/0743554897123002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Microprocess Perspective on Adolescent Identity Development

Abstract: An abundance of research has been conducted on identityformation during adolescence, however, very little is bwwn about the processes that actually drive identity development. Furthermore, limited attention has been paid to the active influence of relationships with parents and peers on identity. Recentl, control theory has-been recognized as a useful framewor*from which to examine the microprocesses involved in identityformation. The purpose of this article is to describe identity development from this microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
1
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 36 publications
1
156
1
8
Order By: Relevance
“…One overarching constructivist model of identity is identity control theory (Grotevant, 1987;Kerpelman, Pittman, & Lamke, 1997;Serpe & Stryker, this volume). This theory assumes that people compare their identity standards -that is, the selfdefining labels that denote who people think they are -to perceptions of themselves obtained through social information and feedback.…”
Section: Prominent Constructivist Models Of Identity Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…One overarching constructivist model of identity is identity control theory (Grotevant, 1987;Kerpelman, Pittman, & Lamke, 1997;Serpe & Stryker, this volume). This theory assumes that people compare their identity standards -that is, the selfdefining labels that denote who people think they are -to perceptions of themselves obtained through social information and feedback.…”
Section: Prominent Constructivist Models Of Identity Formationmentioning
confidence: 99%
“…This theory assumes that people compare their identity standards -that is, the selfdefining labels that denote who people think they are -to perceptions of themselves obtained through social information and feedback. People would continuously compare their internal identity standards to how they are perceived by others and would maintain or alter their identity standards depending on the outcome of this comparison process (Kerpelman et al, 1997). In case there is a match or convergence between identity standards and social perceptions, one would maintain one's identity because it then adequately represents oneself in the social world and, as such, has pragmatic value in providing meaning and in solving problems.…”
Section: Prominent Constructivist Models Of Identity Formationmentioning
confidence: 99%
“…The importance of parents and peers with regard to identity formation has already been demonstrated. In a laboratory setting, Kerpelman and colleagues Kerpelman, Pittman, & Lamke, 1997;Kerpelman, & Pittman, 2001) demonstrated that identity processes were affected by interpersonal communication between adolescents and their friends. Grotevant and Cooper (1985) revealed that observed real-time parent-child interactions triggered identity exploration.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Baumeister, Shapiro, and Tice (1985) suggest that identity crisis occurs when an adolescent encounters circumstances in which he or she lacks enough of a sense of identity to make important life decisions (i.e., an identity deficit) or circumstances that bring to light the incompatibility of two or more aspects of his or her identity (i.e., an identity conflict). As noted, other theorists (e.g., Adams & Marshall, 1996;Breakwell, 1988;Grotevant, 1987;Kerpelman, Pittman, & Lamke, 1997a;Kroger, 1997) have recognized the importance of the transaction between the individual and the individual's context as a potential "starting point" for the identity process (Bosma & Kunnen, 2001). Accordingly, the model ( Figure 5) conceptualizes the CLP's participatory transformative intervention process as a prompt for engagement in the identity crisis (path e).…”
Section: Mediation Among Mediatorsmentioning
confidence: 99%